Treatment Strategies and Survival Outcomes in Breast Cancer - Cheung, Kwok-Leung (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Treatment strategies for breast cancer are wide-ranging and often based on a multi-modality approach, depending on the stage and biology of the tumour and the acceptance and tolerance of the patient. They may include surgery, radiotherapy, and systemic therapy (endocrine therapy, chemotherapy, and targeted therapy). Advances in technologies such as oncoplastic surgery, radiation planning and delivery, and genomics, and the development of novel systemic therapy agents alongside their evaluation in ongoing clinical trials continue to strive for improvements in outcomes. In this Special Issue, we publish a collection of studies looking at all forms of therapeutic strategies for early and advanced breast cancer, focusing on their outcomes, notably survival.